Case report: “Scared to deaf”: medical-legal evaluation of a suspected post -traumatic stress disorder” - Capasso, Emanuele; Marisei, Mariagrazia; Macculi, Marco; Di Lorenzo, Pierpaolo (Frontiers in Psychiatry, 2024)
The case concerns the alleged failure by the resisting administration to fulfill obligations arising from the contract and employment relationship, as well as the violation of safety regulations leading to the workplace accident reported by an Airforce Sergeant. Following the accident, the soldier complains of developing barotraumatic hearing loss with tinnitus and reactive post-traumatic stress disorder to the traumatic event. The case provides an opportunity to analyze the relevance of forensic medical assessment and its integration with psychodiagnostic examination for the correct nosographic classification aimed at evaluating and quantifying biological damage.